Analysis of Students' Computational Thinking Skills on Social Arithmetic Material in Terms of Adversity Quotient - Afifah, Risa Nur; Apriyono, Fikri (Mathematics Dept, Math. and Science Faculty, Universitas Negeri Semarang, 2023)
This research fills an urgent knowledge gap regarding the urgency of analyzing students' computational thinking skills in today's learning. In an era where technology and computing play an important role in daily life, computational thinking skills are crucial for students to face future challenges. Although there have been previous studies on students' computational thinking skills and its influencing factors, there is no adequate understanding on how AQ can affect students' computational thinking skills, especially in the context of social arithmetic learning. This research aims to fill the knowledge gap and analyze how AQ can influence students' computational thinking skills in the context of social arithmetic learning. Through a descriptive qualitative approach, involving 20 students from class VII B MTS Annuriyyah Jember as research subjects. Data were validated using triangulation techniques, namely AQ questionnaire, test and interview. Through the use of AQ questionnaire, the results showed that there were 3 students with Climbers type (high AQ), 14 students with Campers type (medium AQ), and 3 students with Quitters type (low AQ). From each AQ type, three students were selected for further analysis related to their computational thinking ability. The results showed that students with high AQ type were able to fulfill all indicators of computational thinking ability. Students with moderate AQ type were able to identify important information and organize the solution steps, although there were some steps that were not appropriate. However, they were still able to solve the problem correctly. On the other hand, students with low AQ type were unable to record the required information and failed to organize the solution steps properly, resulting in an incorrect solution. Overall, this study showed that students' computational thinking ability in social arithmetic varied depending on their AQ type. The findings indicate a relationship between Adversity Quotient and students' computational thinking skills, which can be used to develop more effective learning strategies and motivate students in learning mathematics.Penelitian ini mengisi kesenjangan pengetahuan yang mendesak terkait urgensi menganalisis keterampilan berpikir komputasional siswa dalam pembelajaran saat ini. Dalam era dimana teknologi dan komputasi memainkan peran penting dalam kehidupan sehari-hari, kemampuan berpikir komputasional menjadi sangat penting bagi siswa untuk menghadapi tantangan masa depan. Meskipun telah ada penelitian sebelumnya mengenai keterampilan berpikir komputasional siswa dan faktor-faktor yang mempengaruhinya, belum ada pemahaman yang memadai mengenai bagaimana AQ dapat mempengaruhi kemampuan berpikir komputasional siswa, terutama dalam konteks pembelajaran aritmatika sosial. Peneitian ini bertujuan untuk mengisi celah pengetahuan tersebut dan menganalisis bagaimana AQ dapat mempengaruhi keterampilan berpikir komputasional siswa dalam konteks pembelajaran aritmatika sosial. Melalui pendekatan deskriptif kualitatif, dengan melibatkan 20 siswa dari kelas VII B MTS Annuriyyah Jember sebagai subjek penelitian. Data divalidasi menggunakan triangulasi teknik, yaitu angket AQ, tes dan wawancara. Melalui penggunaan angket AQ, didapatkan hasil bahwa terdapat 3 siswa dengan tipe Climbers (AQ tinggi), 14 siswa dengan tipe Campers (AQ sedang), dan 3 siswa dengan tipe Quitters (AQ rendah). Dari masing-masing tipe AQ tersebut, tiga siswa dipilih untuk dilakukan analisis lebih lanjut terkait kemampuan berpikir komputasional mereka. Hasil penelitian menunjukkan bahwa siswa dengan tipe AQ tinggi mampu memenuhi semua indikator kemampuan berpikir komputasional. Siswa dengan tipe AQ sedang telah mampu mengidentifikasi informasi penting dan menyusun langkah-langkah penyelesaian, meskipun terdapat beberapa langkah yang tidak sesuai. Namun, mereka masih mampu menyelesaikan permasalahan dengan benar. Di sisi lain, siswa dengan tipe AQ rendah tidak mampu mencatat informasi yang dibutuhkan dan gagal menyusun langkah-langkah penyelesaian dengan baik, sehingga menghasilkan solusi yang salah. Secara keseluruhan, penelitian ini menunjukkan bahwa kemampuan berpikir komputasional siswa dalam materi aritmatika sosial bervariasi tergantung pada tipe AQ mereka. Temuan ini mengindikasikan adanya hubungan antara Adversity Quotient dan keterampilan berpikir komputasioal siswa, dapat digunakan untuk mengembangkan strategi pembelajaran yang lebih efektif dan memotivasi siswa dalam pembelajaran matematika.